(untitled) - McNamara, Tim (Oxford, 2000)
The book examines issues such as test design, the rating process, validity, measurement, and the social dimension of language testing. It looks at both traditional and newer forms of language assessment, and the challenges posed by new views
Keywords: Language and languages; Study and teaching,Methodology